Description of a sauropod dinosaur braincase (Titanosauridae) from the Late Cretaceous Rio Colorado Subgroup, Patagonia - Calvo,Jorge O. (2006)
The fossil record of cranial material from titanosaurid sauropods is very poor and no complete skull has been described so far. Here we describe a new braincase (MUCPv-334) that was recovered from reddish sandstones of the Rio Colorado Subgroup (Late Cretaceous) of the region of Bajo del Añelo, approximately 20 km north of the town Añelo (Neuquén Province, Argentina). This specimen is attributed to the Titanosauridae based on the ventrally projected basipterygoid processes, a common condition shared by other titanosaurids. The robustness of MUCPv-334 together with an unusually expanded crista prootica and the presence of an anterior prolongation of the parasphenoid reaching the basal tubera were not reported in other members of the Titanosauridae, indicating a larger diversity in the braincase morphology of this sauropod clade than previously thought.